Migrant and refugee patient perspectives on travel and tuberculosis along the Thailand-Myanmar border: A qualitative study - Nosten, F; Tschirhart, N; Sein, T; Foster, A (Public Library of Science, 2016)
Background The Thailand-Myanmar border separates two very different health systems. The healthcare system in eastern Myanmar remains underdeveloped as a result of decades of instability. Comparatively, Tak province, Thailand has more healthcare resources. In this Thai border province government hospitals and non-governmental organizations provide tuberculosis (TB) treatment to migrants and refugees. Objectives Our overall study aimed to explore accessibility of TB treatment, TB surveillance and health system responsiveness specific to migrant and refugee populations in Tak province. In this paper, we focus on the perspectives of migrant and refugee TB patients with respect to travel and treatment in Tak province. Methods In 2014 we conducted focus group discussions with 61 TB, Tuberculosis and Human Immunodeficiency Virus co-infection, and multidrug-resistant TB patients in Tak province. We analyzed the data for content and themes and documented individual travel trajectories. Results and Discussion Migrants are travelling with active TB within the country and between Thailand and Myanmar. Migrants primarily travelled to obtain treatment but two participants reported travelling home to seek family care in Myanmar before returning to Thailand for treatment. Travel, while expensive and arduous, is an adaptive strategy that migrants use to access healthcare. Conclusions Migrant’s need for travel points to larger difficulties associated with healthcare access in the border region. Long distance travel with an infectious disease can be seen as an indicator that local healthcare is not available or affordable. These findings suggest that public health officials from both sides of the border should discuss the factors that contribute to travel with active TB and explore potential solutions to mitigate disease transmission in migrant populations.